The decline and fall of the mammalian stem - Neil Brocklehurst (PeerJ, 2024)
The mammalian crown originated during the Mesozoic and subsequently radiated into the substantial array of forms now extant. However, for about 100 million years before the crown’s origin, a diverse array of stem mammalian lineages dominated terrestrial ecosystems. Several of these stem lineages overlapped temporally and geographically with the crown mammals during the Mesozoic, but by the end of the Cretaceous crown mammals make up the overwhelming majority of the fossil record. The progress of this transition between ecosystems dominated by stem mammals and those dominated by crown mammals is not entirely clear, in part due to a distinct separation of analyses and datasets. Analyses of macroevolutionary patterns tend to focus on either the Mammaliaformes or the non-mammalian cynodonts, with little overlap in the datasets, preventing direct comparison of the diversification trends. Here I analyse species richness and biogeography of Synapsida as a whole during the Mesozoic, allowing comparison of the patterns in the mammalian crown and stem within a single framework. The analysis reveals the decline of the stem mammals occurred in two discrete phases. The first phase occurred between the Triassic and Middle Jurassic, during which the stem mammals were more restricted in their geographic range than the crown mammals, although within localities their species richness remained at levels seen previously. The second phase was a decline in species richness, which occurred during the Lower Cretaceous. The results show the decline of stem mammals, including tritylodontids and several mammaliaform groups, was not tied to a specific event, nor a gradual decline, but was instead a multiphase transition.